THE ROLE AND POSITION OF SOCIAL MEDIA AS A SPACE FOR PUBLIC AWARENESS: A PHENOMENOLOGICAL STUDY OF THE MALIKAL MULKI MOSQUE CONFLICT - Haikal Fikri Muztaba; Muhammad Ihsan Mauludin; Ahmad Sarbini; Asep Iwan Setiawan (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2025)
The development of social media over the past twenty years has changed the way society forms, interprets, and disseminates information, including on socio-religious issues. The case of the Malikal Mulki Mosque in Bogor illustrates how the digital space plays an important role in shaping public awareness. This study aims to explore how social media shapes public perception of the dispute, examine the meaning constructed by users through digital interactions, and identify how the dynamics of digital space influence the formation of moral and social awareness in society. A qualitative approach using phenomenological methods is employed to understand the subjective experiences of netizens and the meaning-making processes that emerge in online discourse. Data was collected through virtual observation of posts, comments, and conversations on various platforms such as TikTok, Instagram, and YouTube, then analyzed through stages of reduction, coding, and qualitative interpretation. Research findings show that social media functions as a digital public space that allows people to openly express their emotions, moral values, and views. In the early stages, the discourse was dominated by sentiments of empathy and religious solidarity. As alternative narratives emerged and clarification efforts were made, the public response became more critical, reflective, and focused on evaluating the legal and ethical aspects, as well as the transparency of donation management. Thus, social media does not merely function as a medium for distributing information, but also as an arena for the production of meaning and the process of shaping public awareness that continues to evolve in network-based societies.